2016
DOI: 10.1136/bmjresp-2016-000128
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a metered dose inhaler electronic monitoring device: implications for asthma clinical trial use

Abstract: BackgroundThe SmartTouch Ventolin monitor (Adherium, Auckland, New Zealand) is an electronic monitor for use with a Ventolin metered dose inhaler, which records the date and time of inhaler actuations. This technology has the potential to allow in-depth analysis of patterns of inhaler use in clinical trial settings. The aim of this study was to determine the accuracy of the SmartTouch Ventolin monitor in recording Ventolin actuations.Methods20 SmartTouch Ventolin monitors were attached to Ventolin metered dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…A test based on the suppression of fractional exhaled nitric oxide (FeNO) levels has been used to identify nonadherence to ICS in a difficult asthma population, 24 but electronic counters that can be attached or built within an inhaler represent a direct and less obtrusive method of assessing adherence. 25,26 With these electronic devices, it is possible to monitor whether any improvement in adherence to inhaled therapies can lead to an improvement in asthma control. Alternatively, in some patients, their nonadherence may have been engendered by a true lack of effect of these drugs in controlling asthma in a severe therapyresistant asthma patient.…”
Section: Adherence To Treatmentmentioning
confidence: 99%
“…A test based on the suppression of fractional exhaled nitric oxide (FeNO) levels has been used to identify nonadherence to ICS in a difficult asthma population, 24 but electronic counters that can be attached or built within an inhaler represent a direct and less obtrusive method of assessing adherence. 25,26 With these electronic devices, it is possible to monitor whether any improvement in adherence to inhaled therapies can lead to an improvement in asthma control. Alternatively, in some patients, their nonadherence may have been engendered by a true lack of effect of these drugs in controlling asthma in a severe therapyresistant asthma patient.…”
Section: Adherence To Treatmentmentioning
confidence: 99%
“…The third type of the MDI electronic counter is called SmartTouch Ventolin [21]. This kind of MDI electronic is able to record the date and time, and the actuation number.…”
Section: Current MDI Counter In the Marketmentioning
confidence: 99%
“…PuffMinder Doser [20] Display the available puff of salbutamol on the liquid crystal display (LCD). SmartTouch Ventolin monitor [21] Record the date and time an inhaler is inserted or removed from its case. MDI mechanical counter [23] Using mechanical concept to count the available puff in the MDI canister and display with 3-digit meter.…”
Section: Current MDI Counter In the Marketmentioning
confidence: 99%
“…As with mobile apps, connected devices often secure initial engagement but their long-term clinical benefit is less clear. Although devices such as smart inhalers provide accurate data, 33 they have not yet been studied as part of a holistic behavioral change system. Small studies of the isolated introduction of smart inhalers have not shown an increase in medication adherence or symptom improvement.…”
Section: Current State Of Remote Monitoring and Assessmentmentioning
confidence: 99%